WHEN CHILDREN’S RIGHTS ARE AT STAKE, SHALL COURT REMAIN SILENT? ANALYSIS ON THE IMPLEMENTATION OF PASSIVITY OF JUDGE PRINCIPLE IN CHILD MARRIAGE DISPENSATION IN INDONESIA - Susanti, Laras, Ms (UI Scholars Hub, 2021)
This article explores the existence of asas hakim pasif (passivity of judge principle) in cases involving children in civil cases in Indonesia. As one of the basic principles in civil procedure, judges must be bound by the scope of the case and evidence brought by parties. The principle is not absolute, however, showing that under the Law on Judicial Power; judges are obliged to uphold justice by exploring law and social values more than often. A study case in marriage dispensation shows that judges are facing pluralism orders. Therefore, judges’ value and understanding of children’s rights is a determinant factor. Recently, the Law on Marriage Number 1 of 1974 was amended along with the enactment of Supreme Court Regulation Number 5 of 2019 on Guidance of Marriage Dispensation Examination, which provides better protection for children from child marriage, both in substantive and procedural rights. This article then recommends judges to be more active in deciding on child marriage by upholding the spirit of child protection and encourages the Supreme Court (Mahkamah Agung) to increase its activities to mainstreaming child protection issues.